IMPACT OF BIOFIELD TREATMENT ON GINSENG AND ORGANIC BLUEBERRY YIELD - Sances, Frank; Flora, Eric; Patil, Shrikant; Spence, Amy; Shinde, Vishal (AGRIVITA, Journal of Agricultural Science, 2013)
This study tested the Null Hypothesis for the effect of BioField Energy applied to two separate crops under typical growing conditions, namely ginseng and organic blueberry in commercial plantings in Wisconsin and California, respectively.  Following treatment to replicated plots in standard experimental design, data were collected at harvest for yield quantity and quality.  Ginseng plants treated both pre-harvest and a combination of pre- and post-harvest showed market grade increases of 33.3% and 40.0%, respectively.  Point of sale gross return for this crop is dependent upon tuber quality, and from these data the economics of these treatments were calculated.  Based on stand adjusted yields and quality values, a combination of pre- and post-harvest treatment increased gross income by 57.4%.  The second crop showed similar trends in positive responses. In the two blueberry varieties studied, Emerald treated plants showed 96% statistical increase in yield, while Jewel showed 31% increase.  At the time of treatment, each variety was in a different stage of flowering. The Emerald variety was in the flowering stage, and Jewel was predominately in the fruiting stage. Both treated cultivars however demonstrated increased yield quantity and quality.  The specific mechanisms that lead to these preliminary results need further investigation. Keywords: crop yield, biofield treatment, ginseng, blueberry